Dynamical Contact Problems with Friction Models, Methods, Experiments and Applications - Sextro, Walter (Lecture Notes in Applied Mechanics, 2002)
The aim of this book is to describe an efficient procedure to model dynamical contact problems with friction. This procedure is applied to different practical problems and verified by experiments. Friction contacts are used to transmit forces or to dissipate energy. Examples for dynamical engineering systems with friction are brakes, machine tools, motors, turbines, bearings or wheel-rail systems. A better understanding of friction phenomena can result in improvements like the reduction of noise and maintenance costs, increased life time of machines and improved energy efficiency. Dependent on the features of the friction contact, different contact models and solution methods are applied. The dynamics of elastic bodies in contact are described by a reduced order model through the so called modal description